Genotype/phenotype correlation in Glycogen Storage Disease type IX - Rocha, Hugo (2016)
Glycogen Storage Diseases type IX (GSD IX) are caused by a deficient activity of glycogen phosphorylase kinase and are due to mutations in PHKA1, PHKA2, PHKB or PHKG2. The first two genes are X-linked while the latter two follow an autosomal recessive inheritance. It is a common form of glycogenosis and collectively, defects in these genes are responsible for 25% of all cases of GSD, occurring with a frequency of 1 100,000 live births, with the majority of patients presenting mutation in the X-linked PHKA2 (75% of the cases). Infants with GSD IX present with hepatomegaly, growth retardation and elevated transaminases. Ketotic hypoglycemia and hypotonia may also be present. It most of situations it is a mild GSD, with a benign course, with patients becoming asymptomatic as they grow up. Nevertheless, patients with mutations in the subunit γ (PHKG2) have been associated to more severe phenotypes including increased risk of liver cirrhosis or hepatocelular carcinoma. Our laboratory performs the molecular characterisation of Glycogen Storage Diseases type IX for seven years now (since 2008) and a total of thirteen patients were molecularly diagnosed. From these nine (eight males and one female) present mutation in the X-linked PHKA2, while the remaining three had mutations in PHKG2. Those with mutations in PHKG2 present severe phenotypes, resembling other hepatic GSD’s like GSD I and GSD III, in contrast to those with mutations in PHKA2. Our results allowed not only an easier confirmation of the clinical diagnosis, but also contribute to establish better follow up protocols according to the genotype.